2020
DOI: 10.21203/rs.3.rs-45701/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Dorema Ammoniacum and Acupuncture's Therapeutic Effects in Patients With Ischemic Stroke: A Randomized Controlled Clinical Trial 

Abstract: Aim: Stroke is the third prevalent cause of disability worldwide. This study aimed to evaluate the role of Dorema ammoniacum and acupuncture in the management of patients with stroke.Methods: In this randomized controlled clinical trial, patients with a recent ischemic stroke (within the first month of stroke) were investigated. The patients were divided into three groups. The first group was managed by acupuncture, while the second group received 1 g of Dorema ammoniacum (two 500 mg capsules per day) from amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In Persian traditional medicine textbooks, D. ammoniacum is one of the materia medica that is frequently used for stroke and paralysis as it opens the blood vessels and is also considered as a thrombolytic agent. In traditional medicines, it is used as a remedy by itself and sometimes it is used in combination with other drugs to treat health complications like stroke and paralysis [ 22 ]. The essential oil of D. ammoniacum leaf, fruit, and stem have already been reported to have antioxidant, antimicrobial, and low cytotoxicity activities [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Persian traditional medicine textbooks, D. ammoniacum is one of the materia medica that is frequently used for stroke and paralysis as it opens the blood vessels and is also considered as a thrombolytic agent. In traditional medicines, it is used as a remedy by itself and sometimes it is used in combination with other drugs to treat health complications like stroke and paralysis [ 22 ]. The essential oil of D. ammoniacum leaf, fruit, and stem have already been reported to have antioxidant, antimicrobial, and low cytotoxicity activities [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the second leading cause of death and disability in adults around the world (3,4). Despite the preventable nature of the disease, two-thirds of all stroke deaths occur in developing countries (5)(6)(7). In Iran, studies have reported that the overall in-hospital mortality is 20.5% (8,9), and in comparison to developed countries, stroke is more common, and the mortality rate is higher (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the second leading cause of death and disability in adults around the world (3,4). Despite the preventable nature of the disease, two-thirds of all stroke deaths occur in developing countries (5)(6)(7). In Iran, studies have reported that the overall in-hospital mortality is 20.5% (8, 9), and in comparison to developed countries, stroke is more common, and the mortality rate is higher (10,11).…”
Section: Introductionmentioning
confidence: 99%